Balantidium grimi n. sp. (Ciliophora, Litostomatea), a new species inhabiting the rectum of the frog Quasipaa spinosa from Lishui, China - Zhao Weishan; Li Can; Zhang Dong; Wang Runqiu; Zheng Yingzhen; Zou Hong; Li Wenxiang; Wu Shangong; Wang Guitang; Li Ming (Parasite, 2018)
Balantidium grimi n. sp. is described from the rectum of the frog Quasipaa spinosa (Amphibia, Dicroglossidae) from Lishui, Zhejiang Province, China. The new species is described by both light microscopy (LM) and scanning electron microscopy (SEM), and a molecular phylogenetic analysis is also presented. This species has unique morphological features in that the body shape is somewhat flattened and the vestibulum is “V”-shaped, occupying nearly 3/8 to 4/7 of the body length. Only one contractile vacuole, situated at the posterior body, was observed. The phylogenetic analysis based on SSU-rDNA indicates that B. grimi groups together with B. duodeni and B. entozoon. In addition, the genus Balantidium is clearly polyphyletic.